Innovation of Learning Management System in Mathematics Education Study Program as MBKM Supporting Media - Nasrum, Akbar; Sumpala, Andi Tenri (JME (Journal of Mathematics Education), 2023)
The main objective of this research is to produce an LMS that can support synchronous, asynchronous and blended learning systems, especially in the Mathematics Education study program at Universitas Sembilanbelas November Kolaka (USN Kolaka). This is very important because USN Kolaka currently does not have an independent LMS while the existence of an LMS greatly supports the implementation of MBKM, especially in lecture programs outside the University. The LMS that will be created is an opensource-based LMS that also supports the use of the Woocommerce system. Specifically, the course that will be included in the system is the Mathematics Learning Media course. However, if possible, this LMS will be developed into an online mathematics learning center throughout Indonesia, starting from elementary school to university level. To develop this LMS requires several stages. The first stage is to analyze what essential materials will be included in the system first. Second, designing or designing the LMS interface, menu layout, including how to deliver the material, The third stage realizes what has been planned. The realization stage consists of product trials, evaluation and revision. The last stage is the implementation stage. This stage of development is known as the plompt model. From these stages, an opensource LMS is obtained that is suitable for use as an online learning platform. It can include various lesson materials. Especially for this research, the teaching materials included have also gone through a validation process so that both the material and the media are ready to be used for the teaching and learning process.